The impact of circumferential tumour location on the clinical outcome of rectal cancer patients managed with neoadjuvant chemoradiotherapy followed by total mesorectal excision. Issue 6 (June 2020) - Wang, Xiaojie; Chen, Guangliang; Zhang, Yiyi; Ghareeb, Waleed M.; Yu, Qian; Zhu, Heyuan; Lu, Xingrong; Huang, Ying; Huang, Shenghui; Hou, Dan; Chi, Pan
Abstract: Aim: To investigate the impact of circumferential tumour location on neoadjuvant chemoradiotherapy (CRT) response and its prognostic value for locally advanced rectal cancer (LARC) patients after CRT and surgery. Methods: A retrospective study was performed on 486 patients with LARC who received neoadjuvant CRT and surgical treatment. The rate of pathological complete response (pCR) and survival among patients with anteriorly, laterally, and posteriorly located tumours were compared. Logistic regression was performed to identify pCR predictors. Results: The anterior tumours exhibited the highest pCR rate of 26.7%, which was slightly higher than the 20.0% and 12.3% for lateral and posterior tumours, respectively (P = 0.006). The 5-year Overall survival (OS) rates after CRT were similar among the anterior, lateral, and posterior groups (anterior vs lateral vs posterior: 81.1% vs 89.9% vs 84.1%, P = 0.6368). Multivariate analysis revealed that the circumferential tumour location, post-CRT serum CEA and post-CRT tumour thickness measured by MRI were independently correlated with achieving pCR. Conclusion: This study is the first, to the best of our knowledge, to show that anterior LARC exhibited the highest pCR rate after neoadjuvant CRT. Patients with anterior rectal cancers do not have different prognoses from those with non-anterior cancers if they undergo neoadjuvant CRT.